2019
DOI: 10.1111/bjd.18342
|View full text |Cite
|
Sign up to set email alerts
|

Grading immunohistochemical markers p16 INK4a and HPV E4 identifies productive and transforming lesions caused by low‐ and high‐risk HPV within high‐grade anal squamous intraepithelial lesions

Abstract: Summary Objectives Because current guidelines recognise high‐grade anal squamous intraepithelial lesions (HSILs) and low‐grade SILs (LSILs), and recommend treatment of all HSILs although not all progress to cancer, this study aims to distinguish transforming and productive HSILs by grading immunohistochemical (IHC) biomarkers p16INK4a (p16) and E4 in low‐risk human papillomavirus (lrHPV) and high‐risk (hr)HPV‐associated SILs as a potential basis for more selective treatment. Methods Immunostaining for p16 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…Our findings and previous studies support that E4 expression, as a marker for viral production, can help to further characterise AIN lesions. 19,20 The presence of a methylation positive, E4 negative biomarker pattern, mainly seen in anal cancer, the majority (73.3%) of AIN3 and a proportion (26.7%) of AIN2 lesions is supportive of a high shortterm progression risk to cancer of AIN lesions with this biomarker pattern. Conversely, the presence of an E4 positive, methylation negative biomarker pattern in a high proportion of AIN1 lesions (65.4%) and almost one-third of AIN2 lesions (31.1%) and the near, respectively, complete absence of this biomarker pattern in AIN3 and SCC support our assumption that these lesions have a low risk of progression to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings and previous studies support that E4 expression, as a marker for viral production, can help to further characterise AIN lesions. 19,20 The presence of a methylation positive, E4 negative biomarker pattern, mainly seen in anal cancer, the majority (73.3%) of AIN3 and a proportion (26.7%) of AIN2 lesions is supportive of a high shortterm progression risk to cancer of AIN lesions with this biomarker pattern. Conversely, the presence of an E4 positive, methylation negative biomarker pattern in a high proportion of AIN1 lesions (65.4%) and almost one-third of AIN2 lesions (31.1%) and the near, respectively, complete absence of this biomarker pattern in AIN3 and SCC support our assumption that these lesions have a low risk of progression to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the presence and effect of low-risk HPV types could not be evaluated with the genotyping test used in our study. However, although it has been suggested that low-risk HPV types may have a role in the appearance of anal lesions, the risk of low-risk HPV infection in the development and progression of anal premalignancies is clearly lower than the risk due to high-risk HPV infection [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Griffin et al compared the expression of E4 to p16 INK4A , another host marker, and the hypermethylation of some hostcell genes, which increases with CIN severity. They claim that E4 expression is correlated with low hypermethylation and the absence of p16 INK4A , which is not observed in cervical carcinoma, as described in additional studies [7,96,97].…”
Section: Viral E4 Proteinmentioning
confidence: 90%